Fijación mejorada de N2 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In 1984 the breeding for enhanced N fixation in agronomically acceptable bean cv. was continued. RIZ lines 10, 13, and 29 are performing well in international nurseries. They have high yield, good grain type, broad adaptation, and some disease resistance; however, it is difficult to assess if they support more fixation and get a greater proportion of their N from fixation. As a result, a research project was started which will utilize the (15)N isotope